Navigating Diagnostic Constraints in Pediatric Herpes Simplex Encephalitis: Successful Empirical Acyclovir Therapy without PCR Confirmation - I Kadek Putra Dwipayana; Romy Windiyanto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Herpes simplex encephalitis is an acute or subacute disease associated with focal or global cerebral dysfunction caused by herpes simplex virus type 1 or type 2. Without adequate antiviral administration, the mortality rate reaches 70 percent, with only 9 percent of survivors returning to normal function. While cerebrospinal fluid polymerase chain reaction testing is the gold standard for diagnosis, its availability is severely restricted in resource-limited clinical environments. Case presentation: We report the case of a 4-year-old girl who presented with a profoundly decreased level of consciousness following a five-day history of fluctuating fever. Physical examination revealed a soporific state with a Glasgow Coma Scale of E4V1M1. Initial non-contrast computed tomography of the head was unremarkable. Cerebrospinal fluid analysis demonstrated a mononuclear pleocytosis. Despite the lack of polymerase chain reaction confirmation and the absence of advanced electrophysiological monitoring, the patient was empirically diagnosed with herpes simplex encephalitis based on clinical deterioration and cerebrospinal fluid findings. Immediate management included intravenous acyclovir, dexamethasone, phenobarbital, and supportive care. The patient demonstrated significant clinical improvement and was discharged on day 24 without severe immediate neurological deficits. Conclusion: The absence of molecular diagnostics and advanced neuro-monitoring must not delay the administration of intravenous acyclovir in pediatric patients exhibiting fever and altered mental status. Empirical antiviral intervention remains the most critical determinant of survival and neurological recovery.